2007
DOI: 10.2337/dc06-1600
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Diabetic Foot Ulcer Recurrence in High-Risk Patients

Abstract: OBJECTIVE -The purpose of this study was to evaluate the effectiveness of a temperature monitoring instrument to reduce the incidence of foot ulcers in individuals with diabetes who have a high risk for lower extremity complications.RESEARCH DESIGN AND METHODS -In this physician-blinded, randomized, 15-month, multicenter trial, 173 subjects with a previous history of diabetic foot ulceration were assigned to standard therapy, structured foot examination, or enhanced therapy groups. Each group received therapeu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
427
3
37

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 369 publications
(475 citation statements)
references
References 30 publications
8
427
3
37
Order By: Relevance
“…Regardless if the patient was managed as an inpatient or an outpatient, the remission clinic serves as an integral part of a limb preservation program to maximize ulcer-free, hospital-free, and activity-rich days [2,18]. Individualized patient self-care and monitoring education is a key function of the remission clinic, along with home-based monitoring program coordination, as they have shown to reduce ulcer recurrence [2,1922]. A gradual return to activity is important in extending remission.…”
Section: Step Three: Remission Clinicmentioning
confidence: 99%
“…Regardless if the patient was managed as an inpatient or an outpatient, the remission clinic serves as an integral part of a limb preservation program to maximize ulcer-free, hospital-free, and activity-rich days [2,18]. Individualized patient self-care and monitoring education is a key function of the remission clinic, along with home-based monitoring program coordination, as they have shown to reduce ulcer recurrence [2,1922]. A gradual return to activity is important in extending remission.…”
Section: Step Three: Remission Clinicmentioning
confidence: 99%
“…In ischemic conditions, where blood perfusion may be [100] 2013 1b 1 ---Mori et al [101] 2013 3b 1 ---Najafi et al [102] 2012 2b 1 ---Barriga et al [103] 2012 2b 1 ---Balbinot et al [63] 2012 1b 2 -81.3 46.2 Nagase et al [61] 2011 1b 1 ---Bagavathiappan et al [104] 2010 2b 1 ---Kaabouch et al [105] 2009 3b ----Lavery et al [106] 2007 1a 1 ---Sun et al [107] 2006 2a 1 ---Armstrong et al [108] 2006 3b 1 ---Bharara et al [109] 2006 1b 1 ---Marcinkowska-Gapińska and Kowal [110] 2006 2a 1 ---Sun et al [111] 2005 2a 1 ---Armstrong et al [112] 2003 1b 1 ---Jiang et al [113] 2002 2a 1 ---Fujiwara et al [114] 2000 2a 1 ---Hosaki et al [115] 1999 2b ---Armstrong et al [116] 1997 1b 1 ---Benbow et al [62] 1994 1b 1 ---Stess et al [117] 1986 2a 1 ---Fushimi et al [118] 1985 3b 1 ---Sandrow et al [119] 1972 2-----Brånemark et al [120] 1967 1a ----reduced, especially at the periphery of the human body and limbs (hands and feet), these temperature pattern change [95]. Diabetic foot complications are expensive and they reduce the quality of life for many patients [96].…”
Section: Diabetesmentioning
confidence: 99%
“…Risk identification, education, proper foot care, multidisciplinary treatment, prevision of appropriate footwear and close monitoring are fundamental of DFU management and can help to reduce the amputation rates by 49 − 85% [3,11]. However, Lavery et al pointed out that the incidence of onset of DFUs and lower amputation can be further reduced [5,6].…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…It has been shown that DFUs are the leading causes for hospitalisation and lower extremity amputations; above 85% of all lower extremity amputations in patients with DM resulted from foot ulcerations [17]. Thus, prevention of DFU is one of the foci of any amputation prevention program [5,6]. Researchers and practitioners are challenged to find efficient and effective solutions to avoid DFU and the amputation.…”
Section: Diabetes Mellitusmentioning
confidence: 99%
See 1 more Smart Citation